Remoção de Etinilestradiol no tratamento de água para consumo humano: estudo em escala piloto - Eliane Prado Cunha Costa dos Santos (2011)
In this work a pilot scale study was carried out in order to appraise the removal of the ethinylestradiol micropollutant using five methods of water treatment: i) conventional treatment, also called complete cycle treatment; ii) conventional treatment followed by ultrafiltration; iii) conventional treatment followed by filtration through granular activated charcoal; iv) conventional treatment preceded by chlorine oxidation; v) conventionaltreatment using powdered activated charcoal. Two synthetic waters were used throughout the whole experiment, one with 10 ± 1 uT turbidity and the other with 100 ± 10 uT turbidity. These turbidity standards were chosen because they are representative of the turbidity of thewater sources which supply water to cities in the metropolitan area of Belo Horizonte. Alkalinity of 35,0 ± 5,0 mg · L-1 of calcium carbonate was used and the dose of coagulant (aluminium sulphate) used for all treatment methods analyzed was 22,5 mg · L-1. The conventional treatment was not effective in removal of ethinylestradiol. The remainingconcentrations of ethinylestradiol for the methods of water treatment studied presented significant differences for the conventional treatment followed by filtration through granular activated charcoal and for the conventional treatment preceded by chlorine oxidation, as compared to the other three methods, namely, the conventional treatment, the conventional treatment using powdered activated charcoal, and the conventional treatment followed by ultrafiltration. Using pre oxidation with sodium hypochlorite at the pilot conventional water treatment plant increased efficiency in removal of concentrations of ethinylestradiol. Theremaining concentrations were below the limit of quantification of the method employed, that is, 5,00 ng · L-1.